2022
DOI: 10.1177/08853282221141962
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible phospholipid-based mixed micelles for posaconazole ocular delivery: Development, characterization, and in - vitro antifungal activity

Abstract: Current study intended to prepare and evaluate phospholipid-based, mixed micelles (MMs) to improve the ocular delivery of posaconazole (POS), a broad-spectrum antifungal drug. For this, MMs based on egg phosphatidylcholine (EPC), as the main component, in combination with various bile salts (sodium cholate (NaC), sodium deoxycholate (NaDC), sodium taurocholate (NaTC)) or non-ionic surfactants (Pluronic® F-127, Pluronic® F-68, Tween 80, Labrasol® ALF, and d-a-tocopheryl polyethylene glycol 1000 succinate (TPGS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Previously, we tried using EPC alone (100 mg) to encapsulate etomidate (10 mg), which resulted in large (average particle size > 140 nm) and unstable liposomes with fast drug release (drug release > 80% at 8 h under the same experimental conditions used in this study). Since hybrid drug delivery systems may make use of the advantages of different materials to obtain improved properties such as increased drug loading ability, more spherical shape and better homogeneity of the particles, desirable stability, and sustained drug release, other materials (e.g., Pluronic polymers, Tween 80, and chitosan) have been incorporated into EPC-based formulations [ 49 , 50 ]. In this study, it was hypothesized that the incorporation of lactoferrin together with Pluronic P123 in the EPC liposomes could achieve notably enhanced drug distribution in the brain and improved drug effects.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we tried using EPC alone (100 mg) to encapsulate etomidate (10 mg), which resulted in large (average particle size > 140 nm) and unstable liposomes with fast drug release (drug release > 80% at 8 h under the same experimental conditions used in this study). Since hybrid drug delivery systems may make use of the advantages of different materials to obtain improved properties such as increased drug loading ability, more spherical shape and better homogeneity of the particles, desirable stability, and sustained drug release, other materials (e.g., Pluronic polymers, Tween 80, and chitosan) have been incorporated into EPC-based formulations [ 49 , 50 ]. In this study, it was hypothesized that the incorporation of lactoferrin together with Pluronic P123 in the EPC liposomes could achieve notably enhanced drug distribution in the brain and improved drug effects.…”
Section: Resultsmentioning
confidence: 99%
“…or nonionic surfactants (Pluronic ® F127, Pluronic ® F68, Tween80, Labrasol ® ALF, and d-a-tocopherol polyethylene glycol 1,000 succinate (TPGS)) were prepared to enhance the ophthalmic administration of the broad-spectrum antifungal medication, posaconazole (POS). Studies have shown that phospholipid-based mixed micelles significantly inhibit P-glycoprotein (P-gp)-mediated drug efflux (Osouli et al, 2023). The mean particle size of the polymer nanomicelles approximates 58 nm, demonstrating optimal stability for over a month, a gradual release pattern devoid of any noticeable initial burst, and an elevated level of in vitro antifungal activity.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…13,14 Due to its favorable biocompatibility, biodegradability, and tolerability, P-407 has been employed in drug delivery systems. 15,16 However, its limited mechanical strength and rapid degradation in physiological environment have hindered its clinical application. 14,17 To address these limitations, researchers have incorporated various additives into P-407, such as viscosity modifiers, inorganic salt or crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%